TANTANGAN DALAM PENGIMPLEMENTASIAN KURIKULUM MERDEKA DI JENJANG SEKOLAH MENENGAH ATAS - Damaris Sinaga (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2025)
The implementation of the Merdeka Curriculum in Senior High Schools aims to provide flexibility to schools and teachers in developing more contextual, project-based learning and strengthening student character and competence. This research aims to identify the main challenges in implementing the Independent Curriculum, especially in the aspects of teacher readiness, availability of facilities and infrastructure, and policy support. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with teachers, school principals, and education staff, observation of the learning process, and analysis of related documents. Thematic analysis was used to identify patterns in the informants' experiences regarding curriculum implementation. The research results show that the main obstacles in implementing the Independent Curriculum include a lack of adequate training for teachers, limited supporting infrastructure, and high administrative burdens. In addition, the gap in readiness between schools with adequate and limited resources further widens disparities in the implementation of this curriculum. Even though the government has provided supporting platforms such as Merdeka Mengajar, their use is still limited due to lack of access and ongoing training. In conclusion, the implementation of the Independent Curriculum still faces various challenges that need to be overcome through improving the quality of training, providing supporting facilities, and simplifying administrative burdens. Synergy is needed between the government, schools and teaching staff so that the Independent Curriculum can be implemented effectively and evenly in all high schools in Indonesia.